Do Sunk Costs of Exporting Matter for Net Export Dynamics? - Alessandria, G.; Choi, H. (Quarterly Journal of Economics, 2007)
Firms start and stop exporting. Previous research suggests that these export participation decisions alter the comovement of net exports with the real exchange rate. We evaluate these predictions in a general equilibrium environment. Specifically, assuming firms face an up-front, sunk cost of entering foreign markets, and a smaller period-by-period continuation cost, we derive the discrete entry and exit decisions yielding exporter dynamics in an open economy business cycle model. The model's business cycle exporter dynamics are consistent with that of U.S. exporters. However, in contrast to previous partial equilibrium analyses, model results reveal that export decisions have negligible aggregate effects.